2022
DOI: 10.3389/fpsyt.2022.927128
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Physical Exercise on Cognitive Function of Alzheimer's Disease Patients: A Systematic Review and Meta-Analysis of Randomized Controlled Trial

Abstract: This review aims to systematically review the effects of physical exercise on the cognitive performance of patients with Alzheimer's disease (AD) and its mechanisms of action. Databases such as Web of Science, PubMed, EMBASE, and the Cochrane Central Register of Controlled Trials were searched until December 2021. A randomized controlled trial (RCT) to assess the effect of an exercise intervention (compared with no exercise) on patients with AD. The measures included cognitive function [Mini-Mental State Exami… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
16
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(27 citation statements)
references
References 61 publications
1
16
0
Order By: Relevance
“…Exercise prior to the onset of AD pathology prevents the memory loss and loss of myelin in white matter in the APP/PS1 mouse AD model (Zhang et al, 2017). Physical exercise may improve cognitive function slightly in AD patients (Liu W. et al, 2022).…”
Section: Reversing White Matter Injury Improves Cognition In Animal A...mentioning
confidence: 99%
“…Exercise prior to the onset of AD pathology prevents the memory loss and loss of myelin in white matter in the APP/PS1 mouse AD model (Zhang et al, 2017). Physical exercise may improve cognitive function slightly in AD patients (Liu W. et al, 2022).…”
Section: Reversing White Matter Injury Improves Cognition In Animal A...mentioning
confidence: 99%
“…Clinical trials of mild to moderate exercise in AD suggest a possible beneficial effect in some studies but several studies have not shown efficacy. 7,8 The two patients reported here suggest that vigorous, regular exercise, which has not been studied systematically in MCI or AD, may be needed to slow disease progression in biomarker-positive amnestic MCI or mild AD.…”
Section: Discussionmentioning
confidence: 95%
“…8 This discrepancy may be related to differing selection criteria for studies in meta-analyses, partly because of marked heterogeneity in physical exercise interventions and lack of blindness of raters in most studies. 7,8 Nearly all published studies have evaluated mild to moderate exercise for a few months to 2 years without regular exercise being required during the entire follow-up period. 7 Therefore, the potential diseasemodifying effect of vigorous, regular physical exercise over several years to decades in AD is unknown.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, in VR applications for AD patients, promoting a high level of immersion that corresponds to the experience of feeling "present" in the real world is critical to the patient's response to the intervention. In the available literature, we cannot yet determine whether fully immersive VR technologies are better than moderate or low immersion VR technologies (46)(47)(48).…”
Section: Discussionmentioning
confidence: 99%